2022
DOI: 10.3390/horticulturae8090768
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management of Green Mold Disease of White Button Mushroom Using Botanicals and Biocontrol Agents under Temperate Conditions

Abstract: Green mold (caused by Trichoderma harzianum) is a destructive disease in mushrooms which limits commercial production. The present investigation was carried out to verify the in vitro and in vivo effect of locally available botanicals and bacterial biocontrol agents against this disease. The in vitro evaluation of ethanol extract of botanicals against mycelial growth of T. harzianum at 1, 2, and 3% concentrations showed that Juglans regia and Allium sativum exhibited maximum mycelial growth inhibition of 84.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The search for microbiocontrol possibilities of wet bubble pathogen is focused on antagonists isolating and use from the casing soil to which M. perniciosa shows sensitivity. [ 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies do not use highly active industrial producer strains of polyfunctional biologics with fungicidal activity, which are B. subtilis B-10 and M-22 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The search for microbiocontrol possibilities of wet bubble pathogen is focused on antagonists isolating and use from the casing soil to which M. perniciosa shows sensitivity. [ 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies do not use highly active industrial producer strains of polyfunctional biologics with fungicidal activity, which are B. subtilis B-10 and M-22 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the above producer strains B. subtilis B-10 and M-22 and the well-developed A. bisporus mycelium in the transition stage (popcorn-like generative forms appearing) does not negatively affect morphogenesis [ 20 , 23 ]. Furthermore, the new approaches to the production of polyfunctional biologics via the multibiorecycling of agricultural and industrial wastes have been developed based on a cenotic conception of biorecycling as an extension of the food chain and an expansion of the nutrition supply network [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the successful application of the sustainable, circular substrates, and mushroomcultivation waste reuse, it is also crucial to attend to the sustainable management of diseases, which unfortunately can touch every mushroom grower independently of how careful and precise the production is. This topic was touched upon by Altaf et al [13] in their research, where they investigated the sustainable management of green mold disease (Trichoderma harzianum) of white button mushroom using botanicals and biocontrol agents under temperate conditions. Their study revealed that the integration of botanical and bacterial antagonists in pathogen-infested white-button-mushroom casing reduces green mold infection with corresponding yield gains.…”
mentioning
confidence: 99%